The The Implementation of the Project-Based Learning Model in Teaching Randai Dance within Cultural Arts Education - Elida Elida; Mimi Suriani; Agusti Efi (Journal of Education Research, 2026)
This study examines the implementation of Project-Based Learning in teaching traditional Randai dance. The research aims to explore how Project-Based Learning enhances student engagement, collaboration, and cultural expression. A qualitative approach was employed, involving classroom observations, lesson planning analysis, and project evaluation. The findings indicate that PjBL fosters active student participation, effective group collaboration, and the development of creativity, cultural awareness, discipline, and social responsibility. Teachers successfully designed lesson plans, learning objectives, and project frameworks aligned with Project-Based Learning principles, although adjustments in time allocation and media selection were necessary. The study concludes that integrating Project-Based Learning in teaching Randai Kuantan dance strengthens students’ artistic skills and appreciation of local culture, offering a model for culturally responsive and project-oriented learning in vocational education